Ten-T policy and the Fehmarnbelt tunnel: Impact on regional development between Øresund and Hamburg - Guasco, Clement (Proceedings from the Annual Transport Conference at Aalborg University, 2014)
This article addresses the question of the regional impact of the Ten-T strategy in the Fehmarnbelt region (a region stretching from Malmö to Hamburg), a topic which seems overlooked in the actual discussions on green corridors at the UE level. It presents academic discussions on the matter and sets them in perspective with the current plans for developing a transport corridor across the region and the perception regional transport planning practitioners have on the matter. This article discusses the capacities of those actors to deal with questions regarding the exploitation of Ten-T infrastructure for the benefit of their region. The regional level can also be relevant for integration of sustainable transport solution to the local economic system at a level that national authorities do not have the resources to address. Finally, this article discusses how a regional anchoring allows for the adaptation of such a general EU policy to the local context so that targeted solutions are also adequate for the regions.